Contraceptive use in Flanders (Belgium): A comparison between a general population sample and a Turkish ethnic minority sample. (August 2015) - Elaut, Els; Buysse, Ann; Caen, Maya; Vandamme, Joke; Vermeire, Katrien; T'Sjoen, Guy
Abstract: Objectives To identify contraceptive profiles, and factors affecting these, among women of childbearing age, living in Flanders. Methods The prevalence of knowledge and use of the emergency contraceptive pill (ECP) and contraceptive use is assessed in two samples from the SEXPERT-survey 'Sexual health in Flanders': (i) a population-based sample ( n = 724); and (ii) a probability sample of respondents of Turkish descent ( n = 216). Results Knowledge, but not use, of the ECP is significantly lower among women from the ethnic minority sample, even after correction for income and educational background. A lower educational level is associated with less knowledge of the ECP in both samples. In the general population sample, 16% of sexually active women of childbearing age are at risk of an unplanned pregnancy, compared to 14% of their peers of Turkish origin. These rates are comparable, even after controlling for the different socio-economic status (income and educational level) in both samples. Conclusions Contraceptive profiles of sexually active women of Turkish descent residing in Flanders are mostly similar to those of their counterparts in the general population. Further research is required to develop strategies to improve ECP-knowledge among women with lower educational achievements. Chinese Abstract 摘要 目的 了解居住在比利时佛兰德斯的育龄妇女的避孕方法的使用情况以及相关的影响因素 方法 由"性专家"调研机构进行"佛兰德斯性健康问卷调查"，调查样本分别来自两个人群，一是普通人群（ n =724），二是土耳其后代（第二代移民）（ n =216），了解她们对紧急避孕药的了解和使用情况，以及避孕方法的使用情况。 结果 土耳其妇女对紧急避孕药的了解情况，而不是使用情况，要显著低于普通人群，即便是校正了收入情况和教育背景之后。在这两个人群样本中，对紧急避孕药认知的缺乏均是与低教育水平有关的。在普通人群样本中，16%的性活跃育龄妇女有着非意愿妊娠的风险，而在土耳其人群样本中，该风险为14%。在对这两个人群样本校正了社会——经济要素（收入和教育水平等）之后，这些比例基本相似。 结论 在比利时佛兰德斯，普通人和少数民族土耳其后代的性活跃妇女避孕方法使用情况相似。还需要进一步的研究来找到办法，提高低教育水平的妇女对紧急避孕药的认识。